The Departed: Italian Migration and the American Mafia - Massimo Anelli; Paolo Pinotti; Zachary Porreca (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We document the transplantation of the Sicilian Mafia to the United States in the 1920s, when a large-scale repression campaign in Italy targeted Mafia strongholds and forced many Mafiosi to migrate, and study the resulting short- and long-term effects across neighborhoods in U.S. cities. Using newly linked administrative and historical data from the U.S. Census, Social Security records, and declassified files of the Federal Bureau of Narcotics, we show that neighborhoods hosting enclaves of migrants from Sicilian Mafia strongholds targeted by the repression later became centers of Italo-American Mafia activity. These neighborhoods experienced higher violence, incarceration, and financial exclusion in the short run, but higher income, employment, and educational attainment in the long run. The results suggest that while the arrival of organized criminal networks initially intensified conflict and exclusion, their subsequent consolidation generated localized economic benefits, helping to explain the long-term resilience and persistence of organized crime.
Keywords: K42; F22; N32; R23; D02; 330; organized crime; migration; historical persistence; neighborhood effects